2021
DOI: 10.1007/s10899-021-10073-8
|View full text |Cite
|
Sign up to set email alerts
|

Gambling in Canada During the COVID Lockdown: Prospective National Survey

Abstract: The current study investigated the impact of the COVID pandemic lockdown on gambling and problem gambling in Canada. The AGRI National Project’s online panel participants ( N = 3449) provided baseline gambling data 6 months prior to the pandemic. Re-surveying this sample during the lockdown provided an opportunity to make quantitative comparisons of the changes. Nearly one-third of gamblers reported ceasing gambling altogether during the lockdown. For the continuing gamblers, quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…While previous research has shown that gambling behaviours have decreased or remained the same during the pandemic among many people [ 35 ], some may have turned to or increased their gambling and online gaming in order to distract themselves from the current coronavirus situation. Less frequent gambling due to the pandemic is inherently a good thing, as it is associated with lower gambling-related financial losses and higher self-awareness regarding the possibility that one is spending too much time in the games [ 33 , 43 ]. On the other hand, the social features of games might have provided an alternative way of communicating and building social connections with others while staying socially isolated at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous research has shown that gambling behaviours have decreased or remained the same during the pandemic among many people [ 35 ], some may have turned to or increased their gambling and online gaming in order to distract themselves from the current coronavirus situation. Less frequent gambling due to the pandemic is inherently a good thing, as it is associated with lower gambling-related financial losses and higher self-awareness regarding the possibility that one is spending too much time in the games [ 33 , 43 ]. On the other hand, the social features of games might have provided an alternative way of communicating and building social connections with others while staying socially isolated at home.…”
Section: Discussionmentioning
confidence: 99%
“…Given the evident effects of the COVID-19 pandemic on people's social lives and the social elements inherent to online games, the possibility that motivating social factors influence gambling and gaming participation in the context of the pandemic should be investigated. Importantly, more research is needed on the COVID-specific mental health and social factors, as it is still unknown what the full impact of the COVID-19 pandemic on gambling and gaming will be [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Switching to online gambling: in a United States study, Xuereb et al (2021) report that 15% of participating gamblers had exclusively used offline gambling services before the lockdown and switched to online gambling during the lockdown. Similarly, in a Canadian study, 18% of offline-only gamblers switched to online gambling during the lockdown ( Shaw et al, 2021 ). In New Zealand, however, the figure switching from offline to online gambling was lower (8%) ( Hiringa, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
“…This may be due to divergent gambling regimes or varying COVID-19 restrictions. In Canada, for example, almost all gambling venues were closed ( Shaw et al, 2021 ), while in Australia poker and slot machines were closed nationally for 3 months ( Gainsbury et al, 2021 ), and in Sweden where all casinos were closed, further efforts were undertaken to reduce the time spent on land-based gambling machines (as well as on online casino games) with mandatory limits and other regulations to reduce gambling participation (e.g., limit of deposits) ( Hakansson, 2021 ). Furthermore, the methodological approaches of the studies varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation